2022
DOI: 10.3390/medicina58081058
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Acetabular Cup without Screw Fixation in Total Hip Arthroplasty: A Systematic Review and Meta-Analysis

Abstract: Background and Objectives: Adequate initial fixation of the uncemented acetabular component in total hip arthroplasty is necessary to achieve long-term survival. Although screw fixation contributes to improved cup stability, there is currently no consensus on the use of this method. This study aimed to assess the existing randomized controlled trials (RCTs) on the efficacy and safety of cup fixation in total hip arthroplasty without screws. Materials and Methods: We searched the EMBASE, MEDLINE, Cochrane Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Second, several studies have already reported satisfactory results with the use of the pressfit fixation of a cementless hemispherical cup. However, despite the ongoing controversy regarding the effectiveness of additional screw fixation in many studies reported in the literature [31,32], we believe that it can be helpful in augmenting the stability of cups in cases of hip dysplasia. Screws are not commonly used for acetabular cups during the performance of THA in a normal acetabulum.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Second, several studies have already reported satisfactory results with the use of the pressfit fixation of a cementless hemispherical cup. However, despite the ongoing controversy regarding the effectiveness of additional screw fixation in many studies reported in the literature [31,32], we believe that it can be helpful in augmenting the stability of cups in cases of hip dysplasia. Screws are not commonly used for acetabular cups during the performance of THA in a normal acetabulum.…”
Section: Discussionmentioning
confidence: 87%
“…Finally, conducting additional studies will be needed for an examination of intra-operative measurements of host bone coverage. Several principles must be followed for the achievement of a stable cup fixation in patients with hip dysplasia [29][30][31]. First, ensuring the sufficient contact of the acetabular cup and medial host bone through adequate medialization with a 1 mm or 2 mm press-fit fixation of the hemispherical acetabular cup is important in order to overcome the challenge posed by the shallow cotyloid fossa and small acetabulum of patients with hip dysplasia.…”
Section: Discussionmentioning
confidence: 99%